A retrospective analysis of post-treatment complications in patients with carcinoma vulva undergoing surgery as a primary treatment modality - Balamurugan G; Senthil Kumar N; Ramkumar P; Selvaraj N (Asian Journal of Medical Sciences, 2024)
Background: Vulvar carcinoma accounts for 5% of all malignant neoplasms in the female genital tract, with a higher incidence in developing countries and increased risk associated with human papillomavirus (HPV) infection. Aims and Objectives: The study aimed to retrospectively evaluate treatment complications in patients with carcinoma vulva who had undergone primary surgery alone or as part of multimodality therapy. It also aimed to evaluate HPV marker positivity in this group of patients and its relation to disease profile and prognosis. Materials and Methods: This is a retrospective study wherein data from the Regional Cancer Centre, Coimbatore, from 2017 to 2023, about 42 patients who underwent primary surgery for carcinoma vulva were analyzed. Patient information, including age, symptoms, imaging, biopsy, staging, and treatment options, were retrieved for analysis. Results: Regarding post-operative complications, ten patients developed seroma (23%), 9 had limb edema (21%), five patients had wound dehiscence (11%), and nine patients had post-radiotherapy/chemotherapy complications (21%). The mortality rate among patients in the study was 9% (4 patients). All four died because of nodal relapse. Six patients (14%) had disease recurrence in this study group, among whom 5 were HPV-negative (83%). Two patients had a recurrence in the primary site, and four had a nodal recurrence. HPV marker p16 was positive in 18 patients (43%) overall, and they were found to belong to the younger age group and had good treatment outcomes. Conclusion: Primary surgery for carcinoma vulva patients in our study is associated with limited but manageable complications amenable to rectification. HPV-associated carcinoma vulva is increasing in prevalence (43% in younger age group) with a positive prognosis.